Pengembangan E-Modul Karier Wirausaha Berbasis UMKM Lokal dengan Model Rowntree untuk Siswa SMAN 6 Sidrap - Nur, Edil Wijaya; Saman, Abdul; Buchori, Sahril (JURNAL KONSELING GUSJIGANG, 2024)
This study aims to develop an E-Module for Entrepreneurship Career Guidance, based on local UMKMs, tailored for students at SMAN 6 Sidrap. Utilizing Rowntree's development model, the research integrates essential components from student needs analysis, collaboration with career counselors, and case studies of successful local entrepreneurs. The novel aspect of this E-Module lies in its focus on local UMKMs in Sidrap, providing students with relatable and inspiring examples of entrepreneurship. Findings indicate that the E-Module significantly enhances students' self-efficacy and interest in pursuing entrepreneurial careers. It also aligns with the Social Cognitive Career Theory (SCCT), supporting students in understanding entrepreneurial opportunities and fostering realistic career expectations. By including practical simulations and real-life success stories, the E-Module creates a dynamic and engaging learning environment, demonstrating its effectiveness as a career guidance tool.